Can the Hometown Also Be the Ideology? - Bogook Kim (Asian Studies)
This article chronicles the life of Choi Inhwan, focusing on his movements across North Korea, Hungary, Federal People’s Republic of Yugoslavia, and Switzerland in the 1950s. Choi’s North Korean background is traced, with scant details available after his return in 1960. Born in 1934 to ordinary farmers, Choi’s early education spanned from primary school to high school in Uiju, North Pyongan Province. His academic journey continued in Hungary (1953‒1957), where he faced language challenges but excelled in Hungarian and biology at Budapest Medical University. His involvement in the 1956 Hungarian Revolution is highlighted by multiple sources, confirming his active participation and subsequent escape to Yugoslavia, followed by relocation to Switzerland as a political refugee in 1957.